Pre-marital Sexual Behavior of Adolescents: The Influence of Self-Control, Parental Attachment, and Peer Roles: Pre-marital Sexual Behavior of Adolescents: The Influence of Self-Control, Parental Attachment, and Peer Roles - Zahro Malihah; Melly Latifah; Dwi Hastuti (Journal of Family Sciences, 2022)
Pre-marital sexual behavior in adolescents is influenced by personal, family, and environmental factors, including peer groups. This study aims to analyze the influence of adolescent-parental attachment, self-control, and the role of peers on the pre-marital sexual behavior of high school/vocational high school adolescents. This explanatory research was conducted purposively at SMA and SMK in Bogor city. Data collection was carried out voluntarily using a questionnaire via google form in January 2022. Respondents in this study were 245 teenagers who had unmarried criteria and still had intact parents. The results showed that the majority of adolescent pre-marital sexual behavior was in the "never" category (86.7%), only 1.6% were included in the "always" category. Furthermore, most adolescents have moderate self-control (48.6%), almost half (44.9%) have an attachment to their father in the "moderate" category, more than half of adolescent-mother attachments are in the "good" category (50.6%), while almost half of in the "very good" category in positive peer roles (47.8%). In addition, it was revealed that there was a negative influence between the role of peers and the tendency of pre-marital sexual behavior.